Novel combination strategies for enhancing efficacy of immune checkpoint inhibitors in the treatment of metastatic solid malignancies. (22nd September 2017) - Flynn, Michael J.; Larkin, James M.G.
ABSTRACT: Introduction : Immune-checkpoint inhibitor (ICPI) drugs, which include antibodies against CTLA-4, PD-1 and PD-L1, have been shown to induce durable complete responses in a proportion of patients with particular efficacy demonstrated in both the first line and refractory setting in advanced NSCLC and melanoma. However, these drugs remain effective only in a minority of unselected patients. Areas covered : This review will focus on mechanisms of resistance to ICPI and underline the importance of identification of novel predictive markers of responsiveness. The rationale for the combination of ICPI with specific chemotherapies, targeted therapies and other immuno-oncology drugs in order to improve efficacy will be provided. Expert opinion : There are near-endless permutations of combination strategies of these agents with ICPI that have become feasible treatment strategies. Development of an understanding of resistance mechanisms to ICPI by a shift towards translational approaches to comprehensive genomic profiling and interrogation of the tumor microenvironment will encourage recruitment of patients into biomarker-driven combination trials. More than ever, industry professionals, clinicians and scientists will need to collaborate to increase the investment in clinical trials of those therapeutic agents and combination strategies which are most likely to be transformative for patients.